Heimlich Valve as Ambulatory Treatment for Persistent Pneumothorax in a Patient with Pulmonary Tuberculosis: A Case Report and Literature Review - Haryati Haryati; Bagus Wicaksono; Desi Rahmawaty (Journal of Cardio-Thoracic Medicine, 2022)
Tuberculosis (TB) is still a significant medical and social problem in developing nations like Indonesia, with high morbidity and mortality rates. Tuberculosis infection are mostly found in the lungs, but they can affect other organs as well. Secondary spontaneous pneumothorax (SSP) is one of the most serious complications of tuberculosis, requiring the insertion of a chest tube in the majority of cases. The Heimlich valve can be used in complicated and persistent pneumothorax. The Heimlich valve may be outdated, but it is a very efficient one-way valve that provides safe air evacuation from the thoracic cavity. A 53-year-old man was hospitalized after complaining of left-sided chest discomfort and shortness of breath. The patient confirmed receiving tuberculosis treatment four years ago. During a physical examination, hyperresonance to percussion and decreased vesicular breath sounds was found on left side, wheezing on the right, and SaO2 of 92% in room air. An x-ray of the chest revealed a left side pneumothorax and fibrosis at the right lung's apex. Emergency drainage was done and an X-ray evaluation of  the collapsed lung aeration was observed. However, even though drainage has been done for 19 days, an examination revealed persistent pneumothorax, requiring extended drainage. Due to a lack of resources and to prevent prolonged hospitalization, we began using a Heimlich valve to treat pneumothorax. The chest tube and Heimlich valve were detached successfully after two months. In conclusion, the Heimlich valve provides a practical and affordable treatment for ambulatory care of persistent pneumothorax.